Fluent or nonfluent? Part A. Underlying contributors to categorical classifications of fluency in aphasia. Issue 5 (3rd May 2020) - Clough, Sharice; Gordon, Jean K.
ABSTRACT: Background: The concept of fluency is widely used to dichotomously classify aphasia syndromes in both research and clinical practice. Despite its ubiquity, reliability of fluency measurement is reduced due to its multi-dimensional nature and the variety of methods used to measure it. Aims: The primary aim of the study was to determine what factors contribute to judgements of fluency in aphasia, identifying methodological and linguistic sources of disagreement. Methods & Procedures: We compared fluency classifications generated according to fluency scores on the revised Western Aphasia Battery (WAB-R) to clinical impressions of fluency for 254 English-speaking people with aphasia (PwA) from the AphasiaBank database. To determine what contributed to fluency classifications, we examined syndrome diagnoses and measured the predictive strength of 18 spontaneous speech variables extracted from retellings of the Cinderella story. The variables were selected to represent three dimensions predicted to underlie fluency: grammatical competence, lexical retrieval, and the facility of speech production. Outcomes & Results: WAB-R fluency classifications agreed with 83% of clinician classifications, although agreement was much greater for fluent than nonfluent classifications. The majority of mismatches were diagnosed with anomic or conduction aphasia by the WAB-R but Broca's aphasia by clinicians. Modifying the WAB-R scale improved the extent to which WAB-R fluency categories matched clinical impressions. Fluency classifications were predicted by a combination of variables, including aspects of grammaticality, lexical retrieval and speech production. However, fluency classification by WAB-R was largely predicted by severity, whereas the presence or absence of apraxia of speech was the largest predictor of fluency classifications by clinicians. Conclusions: Fluency judgements according to WAB-R scoring and those according to clinical impression showed some common influences, but also some differences that contributed to mismatches in fluency categorization. We propose that, rather than using dichotomous fluency categories, which can mask sources of disagreement, fluency should be explicitly identified relative to the underlying deficits (word-finding, grammatical formulation, speech production, or a combination) contributing to each individual PwA's fluency profile. Identifying what contributes to fluency disruptions is likely to generate more reliable diagnoses and provide more concrete guidance regarding therapy, avenues we are pursuing in ongoing research.